2014
DOI: 10.1080/10410236.2013.863139
|View full text |Cite
|
Sign up to set email alerts
|

Structurational Divergence Theory as Explanation for Troublesome Outcomes in Nursing Communication

Abstract: Structurational divergence (SD) theory captures negative communication cycles resulting from interpenetration of incompatible meaning structures. It is estimated that 12-15% of practicing nurses suffer from a problematic level of SD. With a sample of 713 nurses (57 departments) in a large hospital, this study tests a model positing SD as a root explanation of nursing job satisfaction and turnover. A number of variables long presumed to be explanations for job satisfaction and turnover were hypothesized as medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 75 publications
(92 reference statements)
1
27
0
Order By: Relevance
“…Inter-professional communication within the health care team is also essential for providing effective health care. Quality of team cooperation and communication plays a vital part in fostering a healthy work environment, increasing job satisfaction, preventing burnout syndrome and lowering health care professionals' intentions to leave [3][4][5]. Some studies have also demonstrated a relationship between the effectivity of communication and the occurrence of medical errors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Inter-professional communication within the health care team is also essential for providing effective health care. Quality of team cooperation and communication plays a vital part in fostering a healthy work environment, increasing job satisfaction, preventing burnout syndrome and lowering health care professionals' intentions to leave [3][4][5]. Some studies have also demonstrated a relationship between the effectivity of communication and the occurrence of medical errors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the struggles they faced could be attributed to larger institutional issues creating a nexus of incompatible structures exerting equally compelling demands of contradictory meaning systems (Nicotera & Clinkscales, 2010). These nurses experienced all of the difficulties outlined below, which were confirmed in subsequent quantitative research to be empirically linked to SD (Nicotera et al, 2015;Nicotera & Mahon, 2013).…”
Section: Sd In Nursingmentioning
confidence: 88%
“…The SD-cycle is a negative communication spiral: unresolvable conflict (often manifesting in interpersonal relations), immobilization (inability to achieve goals), and erosion of development that perpetuates the contradiction (see Figure 1). SD has been observed in nursing, and several negative implications associated with SD have been reported including burnout, high turnover, and bullying (Nicotera & Clinkscales, 2010;Nicotera et al, 2015;Nicotera & Mahon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have demonstrated a relationship between the work environment and medical errors (Flynn et al 2010, Kramer et al 2011. Communication and collaboration have been associated with nurses' attachment to their organisation and improved nurse retention (Townsend-Gervis et al 2014, Nicotera et al 2015. For nurses, working in a hospital with a good work environment is associated with a significantly lower likelihood of experiencing burnout, job dissatisfaction and an intention to leave ).…”
Section: Healthy Work Environment and Group Interactionmentioning
confidence: 99%
“…, Nicotera et al . ). For nurses, working in a hospital with a good work environment is associated with a significantly lower likelihood of experiencing burnout, job dissatisfaction and an intention to leave (Aiken et al .…”
Section: Introductionmentioning
confidence: 97%